The Impact of Emotional Intelligence on Emotional Contagion: Implications for Teams (Journal of Organizational Psychology, 2021)
This study focuses on exploring the relationship between Emotional Intelligence (EI) and Emotional Contagion (EC) in teams, and on understanding the effect of regulated emotions (EI) on spontaneous emotions (EC). Analysis quantitatively determined the extent EI impacts EC, and which factors of EI are most important to positive change in EC. Results of this study have practical implications for strengthening team effectiveness, and ultimately increasing the potential for positive team outcomes.
Keywords: organizational psychology; emotional intelligence; emotional contagion; teamwork; collaboration